Evaluation of white and yellow grain corn hybrids (Zea mays L.) in environments of Central America, Panama and the Caribbean in 1996. - Aguiluz, Adán (2016)
Thirty white-grain hybrids in 1210cations and 20 yellow-grain hybrids in 14 locations were evaluated in 1996. The control HB-83 was used for white grains, and control HB-46 was used for yellow grains. Measurement of genotype/environment interaction was obtained through the analysis of additive main effects and multiplicative in~eractions (AMMI model). White hybrids A- 7573, H-53, HN-951, A-7530, CB- XHS-7GMl and CML- 9XCML-47 equaled or surpassed the HB-83 control in 17,8%; 0,1%; 1,1%; 9,2%; 8,1% and 18,7% ofthe cases, respectively, showing little interaction with the environment (AMMI values close to O). Two of these hybrids are from national programs, and three from private seed companies. As for the yellow grains, only the CB-XHS-8GM3, HS-6 and DK-888A hybrids surpassed the control HA-46 in yield, and showed AMMI scores c10se to O: (0,20; -0,07 and -0,12, respectively); all of these belong to private seed companies.